Language and Cultural Adaptation of Non-Javanese Students at Mambaus Sholihin Boarding School: Islamic Education Perspective - Miswanto, Miswanto; Julfi, Alfath; Pradita, Ega Krisna; Najmi, Akmalun (State Islamic Institute of Manado (IAIN) Manado, Indonesia, 2025)
This study aims to analyze the language and cultural adaptation process of non-Javanese students at the Mambaus Sholihin Islamic Boarding School, Gresik, East Java. The focus of the study includes: (1) language adaptation in daily communication, (2) cultural adjustment to the norms, traditions, and rhythm of Islamic boarding school life, (3) the role of social support from peers, administrators, and ustadz, and (4) adaptation challenges experienced by students in the initial phase of boarding. This study uses a qualitative approach with a phenomenological design. Data were collected through in-depth interviews, non-participatory observation, and documentation of six non-Javanese students as primary informants and three ustadz as supporting informants, who were selected purposively. Data analysis was carried out using an interactive model that includes data reduction, data presentation, and drawing conclusions. The results of the study indicate that non-Javanese students face initial difficulties in the form of limited basic facilities, Javanese language barriers, academic difficulties in learning Pegon-based yellow books, and adjustment to the strict Islamic boarding school discipline system. However, the adaptation process is gradual and shows positive developments through peer support, guidance from administrators, and the adaptive and inclusive pedagogical approach of the ustadz. These findings confirm that Islamic boarding schools serve as spaces for cultural integration and character development for students. The implications of this research emphasize the importance of responsive mentoring and communication strategies to support the adaptation of new students within the context of Islamic Religious Education.